Pengendalian Banjir Sungai Garang Melalui Upaya Peningkatan Elevasi Mercu Tanggul, Luas Penampang Basah Sungai dan Pengurangan Debit Banjir - Sutopo, Yeri (Semarang State University, 2006)
Abstract: The purposes of this research were (1) Ã‚Â to explain the ability of Garang river existing condition to flood control at the 100 years flood retum period (Q100); (2) to find out the proportional and combination simultaneously efforts (technically) on flood control at Garang river that can anticipate overtopping at both, westside ang eastside of the river, due to its 100 years flood retum period. This research had use the secondary data analysis method. Data collecting were Garang river. water level elevation at Panjangan (AWLR), river cross section, Simongan weir cross section, along river, figures of AWLR instrument site and TTG level at Panjangan, also data about tidal elevation atÃ‚Â Garang river estuary. The data manually compiled, furthermore by DUFLOW The result of this research were: (1) Garang river didn't have any ability to control water level elevation at 100 years flood return period (Q100), the dam along Menorah and Panjangan to the North of Tanah Mas housing has flood run-off; (2) an effort by raising the dam crest elevation of Garang river in the amount of 20% from existing; increase river channel cross section damp Ã‚Â area in the amount of 30% from existing; and decrease the 100 Years (Q100) plan discharge in the amount of 50% technically has the maximal influence about damping of the flood water level elevation.Abstrak: Tujuan penelitian ini adalah Ã‚Â (1) Menjelaskan kemampuan Sungai Garang pada kondisi eksisting dalam meredam banjir pada kala ulang banjir 100 tahunan (Q100); (2) Menemukan proporsi kombinasi upaya pengendalian banjir (teknis) secara simultan yang mampu mengatasi terjadinya limpasan di atas tanggul sebelah Barat maupun Timur (over topping) karena debit banjir 100 tahunan (Q100) Ã‚Â di Sungai Garang. Metode yang digunakan pada penelitian ini adalah analisis data sekunder. Data yang dihimpun adalah elevasi muka air sungai Garang di Panjangan (AWLR), tampang sungai, tampang bendung Simongan, tampang memanjang sungai, gambar letak instrumen AWLR dan ketinggian TIG di Panjangan, serta elevasi pasang surut di Muara Sungai Garang. Data-data itu dikompilasi secara manual, yang selanjutnya dimodelkan dengan aplikasi DUFLOW. Hasil penelitian ini adalah: (1) Sungai Garang tidak mempunyai kemampuan dalam meredam elevasi muka air banjir, Ã‚Â tanggul di sepanjang Menoreh dan Panjangan sampai dengan ujung Utara Perumahan Tanah Mas terlimpas oleh Banjir,(2) upaya peningkatan elevasi mercu tanggul Sungai Garang sebesar 20% dari kondisi eksisting; peningkatan luas penampang basah sebesar 30% dari kondisi eksisting; dan pengurangan debit rencana seratus tahunan (Q100) sebesar 50% secara teknis mempunyai pengaruh paling maksimal terhadap peredaman elevasi muka air banjir.